The effectiveness of a counseling program based on recalling past memories (Reminiscence) to reduce symptoms of depression in the elderly people - Hamad, Assistant Professor Dr. Nadira Jameel; kareem, Instructor:DR. Hussein majid (The journal of contemporary issues in business and government, 2021)
The aim of the current research is to identify the effectiveness of the program to retrieve past memories (Reminiscence) in adults of (65-75) years old, by (14) elderlies in the experimental group and (14) elderlies in the control group, then the researcher conducted the equivalent between the two groups in variables (Age, educational level, marital status, and their scores on the psychological depression scale), then the researcher designed a consulting program to retrieve past memories related to childhood, elementary school, intermediate and secondary schools, work, marriage, children, holidays and events, and the number of sessions reached (10) sessions at a rate of two sessions per week and the session time (90 minutes), and after applying the program to retrieve past memories (Reminiscence) on the experimental group, the results of the statistical analysis showed the following: There are statistically significant differences in the post-measurement between the experimental group and their peers in the control group in favor of the experimental group on the psychological depression scale. The presence of statistically significant differences between the averages of the pre- measurement grades and the post-measurement in favor of the post-application on the scale of psychological depression. There are no statistically significant differences between the experimental group's grades in the post and tracer measures on the psychological depression In light of the results of the current research, the researcher developed a set of recommendations and proposals.